Accounting Measurement Rules in the Presence of Higher-Order Uncertainty - Stocken, Phillip C.; Zhang, Gaoqing (The Accounting Review, 2025)
ABSTRACT We study the investment efficiency of the historical cost and fair value measurement rules when a reporting firm and its investors confront higher-order uncertainty inferring the behavior of others. Although all investors are attentive to the firm’s report, the firm and investors incorrectly believe only some investors are attentive. We find that a report prepared under the historical cost rule yields greater investment efficiency than under the fair value rule if and only if (1) the investors are badly calibrated, (2) the firm’s production technology exhibits sufficiently strong returns to scale, (3) the firm’s productivity realization is sufficiently negatively correlated with market returns, and (4) the firm is sufficiently well calibrated about its investors’ attentiveness. JEL Classifications: C72; D80; D83; M41.